Improvement of Butamben Anesthetic Efficacy by the Development of Deformable Liposomes Bearing the Drug as Cyclodextrin Complex - Paola Mura; Francesca Maestrelli; Marzia Cirri; Giulia Nerli; Lorenzo Di Cesare Mannelli; Carla Ghelardini; Natascia Mennini (MDPI AG, 2021)
This work was aimed at enhancing butamben (BTB) anesthetic efficacy by the "drug-in cyclodextrin (CD)-in deformable liposomes" strategy. In the study, phase-solubility studies with natural (α-, β-, γ-) and derivative (hydroxypropyl-α-and β-, sulfobutylether-β, methyl-β) CDs evidenced the highest BTB affinity for βCD and its derivatives and indicated methyl-βCD (RAMEB) as the best carrier. Drug-RAMEB complexes were prepared by different techniques and were characterized for solid-state and dissolution properties. The best BTB-RAMEB product was chosen for entrapment in the aqueous core of deformable liposomes containing stearylamine, either alone or with sodium cholate, as edge activators. Double-loaded (DL) liposomes, bearing the lipophilic drug (0.5% w/v) in the bilayer and its hydrophilic RAMEB complex (0.5% w/v) in the aqueous core, were compared to single-loaded (SL) liposomes bearing 1% w/v plain drug in the bilayer. All vesicles showed homogeneous dimensions (i.e., below 300 nm), high deformability, and excellent entrapment efficiency. DL-liposomes were more effective than SL ones in limiting drug leakage (<5% vs. >10% after a 3 months storage at 4 °C). In vivo experiments in rabbits proved that all liposomal formulations significantly (p < 0.05) increased the intensity and duration of drug anesthetic action compared to its hydroalcoholic solution; however, DL liposomes were significantly (p < 0.05) more effective than SL ones in prolonging BTB anesthetic effect, owing to the presence of the drug-RAMEB complex in the vesicle core, acting as a reservoir. DL liposomes containing both edge activators were found to have the best performance.